Impact Characteristics of Different Rocks in a Pulsed Laser Irradiation Experiment: Simulation of Micrometeorite Bombardment on the Moon. Issue 10 (9th October 2017) - Wu, Yanxue; Li, Xiongyao; Yao, Wenqing; Wang, Shijie
Abstract: Without the protection of the atmosphere, the soils on lunar surfaces undergo a series of optical, physical, and chemical changes during micrometeorite bombardment. To simulate the micrometeorite bombardment process and analyze the impact characteristics, four types of rocks, including terrestrial basalt and anorthosite supposed to represent lunar rock, an H‐type chondrite (the Huaxi ordinary chondrite), and an iron meteorite (the Gebel Kamil iron meteorite) supposed to represent micrometeorite impactors, are irradiated by a nanosecond pulse laser in a high vacuum chamber. Based on laser irradiation experiments, the laser pits are found to be of different shapes and sizes which vary with the rock type. Many melt and vapor deposits are found on the mineral surfaces of all the samples, and nanophase iron (npFe) or Fe‐Ni alloy particles are typically distributed on the surfaces of ilmenite, kamacite, or other minerals near kamacite. By analyzing the focused ion beam ultrathin slices of laser pits with a transmission electron microscope, the results show that the subsurface structures can be divided into three classes and that npFe can be easily found in Fe‐bearing minerals. These differences in impact characteristics will help determine the source material of npFe and infer the type of micrometeorite impactors. During micrometeorite bombardment, in the mare regions, the npFe are probably produced simultaneously from lunar basalt and micrometeorites with iron‐rich minerals, while the npFe in the highlands regions mainly come from micrometeorites. Plain Language Summary: Micrometeorite bombardment of the surfaces of planetary bodies without the protection of atmosphere is a common phenomenon that changes the physical and chemical properties of soils exposed on the airless lunar surface. To understand the micrometeorite bombardment process and analyze systematically the impact characteristics, we designed a pulsed laser irradiation experiment which could simulate the micrometeorite bombardment. The results show that the subsurface structures of minerals irradiated by a pulsed laser can be divided into three classes and that nanophase iron inclusions can be easily found in Fe‐bearing minerals. Characteristics of subsurface structure and inclusions are related to rock type and mineral composition. So these differences in impact characteristics will help determine the source material of nanophase iron and infer the type of micrometeorite impactors. During micrometeorite bombardment, in the mare regions, nanophase iron are probably produced simultaneously from lunar basalt and micrometeorites with iron‐rich minerals, while the nanophase iron in the highland regions mainly come from micrometeorites. Key Points: Different impact characteristics of samples related by micrometeorite bombardment are studied through pulsed laser irradiation experiments Characteristics of subsurface structure and inclusion are related to rock type and mineral composition The structure and inclusion of lunar soil grain will help determine the source of npFe and infer the types of micrometeorite impactors